Evaluation of analgesic, neuropharmacological and cytotoxic activity of Trigonella foenum-graecum Linn. - Akter, Moli; Afroze, Mirola; Khatun, Ambia (International Current Pharmaceutical Journal, 2011)
The present study was carried out to investigate the possible analgesic, neuropharmacological and cytotoxic activities of the methanolic extract of Trigonella foenum-graecum Linn. leaves. The analgesic and neuropharmacological activities of Trigonella foenum-graecum Linn. were investigated at the doses of 100mg/kg, 200mg/kg and 400mg/kg of body weight in mice. Analgesic potential of the extract was evaluated for centrally acting analgesic property using tail immersion method and peripheral analgesic actions using acetic acid-induced writhing test. In acetic acid-induced writhing test, extract produced a significant (p < 0.001) inhibition of writhing response in a dose dependent manner but maximum inhibition (93.46%) of writhing was found at 400mg/kg dose. In tail immersion method, extract caused a significant (p < 0.001) increase in latency time and the results were comparable to the standard drug Diclofenac- Sodium. In addition, neuropharmacological property of crude extract was carried out by Hole cross and Open field test. The extract significantly (p < 0.05-0.001) displayed a dose dependent suppression of motor activity, exploratory behaviour. Furthermore, the extract was subjected to Brine Shrimp lethality bioassay for primary evaluation of cytotoxicity, where the extract was found to be highly toxic to Brine Shrimp nauplii, having LC50 values of 10μg/ml while the LC50 of the reference anticancer drug vincristine sulphate was 0.66μg/ml. The results of this present study suggest that the extract possesses analgesic, cytotoxic and CNS depressant activities. Key Words: Trigonella foenum-graecum Linn.; cytotoxicity; neuropharmacological; analgesic activity. DOI: http://dx.doi.org/10.3329/icpj.v1i1.9218 International Current Pharmaceutical Journal 2011, 1(1): 6-11